2010
DOI: 10.1103/physrevb.82.094102
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen interaction with point defects in tungsten

Abstract: First-principles calculations were used in determining the binding and trapping properties of hydrogen to point defects in tungsten. Hydrogen zero-point vibrations were taken into account. It was concluded that the monovacancy can hold up to five hydrogen atoms at room temperature. The hydrogen was found to distort the self-interstitial atom configuration geometry. The interaction of hydrogen with the transmutation reaction impurities Re and Os were studied. It was found that the substitutional Re and Os have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
161
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(197 citation statements)
references
References 55 publications
(55 reference statements)
28
161
0
6
Order By: Relevance
“…Ab initio and Molecular Dynamics simulations showed that H tends to occupy off-centred position in a vacancy, experiencing weak attraction to W atoms [18,19]. This implies that H atoms, when filling a void, first should occupy the inner surface positions and then fill the centre.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Ab initio and Molecular Dynamics simulations showed that H tends to occupy off-centred position in a vacancy, experiencing weak attraction to W atoms [18,19]. This implies that H atoms, when filling a void, first should occupy the inner surface positions and then fill the centre.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The primary D-W irradiation-induced collision statistics were determined by binary collision approximation calculations with SRIM and the W collision cascades by Molecular Dynamics (MD) [65] simulations. The activation energies needed for detrapping of D from the resulted irradiation-induced trap sites were determined with first-principles calculations using electron density functional theory (DFT) [64]. A full, detailed description of the present RE method and its inputs from MD and DFT calculations have been published recently [66a] The validated RE code is suitable for simulating hydrogen implantations into W with fluences below the blistering threshold.…”
Section: Simulationmentioning
confidence: 99%
“…For the EAM1 potential, emphasis was put on a quantitative reproduction of ab initio data for the binding between H-H, He-He and H-He pairs [11]. The off-center position of a H atom in a vacancy as predicted by DFT [14] was not considered, and therefore both H and He are described by pair potentials only. For the EAM2 potential, the focus was made on the stabilizing H in an off-center position in the vacancy and therefore an embedding function was added for H. Both types of the potentials predict the tetrahedral position for a H atom as the most favorable in bulk W, which is important for this work as we focus on the calculation of the binding between H atoms and defects.…”
Section: Computational Detailsmentioning
confidence: 99%